Navigating Publishing Critical Health Communication Research - Hudak, Nicole (Frontiers in Communication, 2020)
Publishing critical health communication scholarship comes with challenges. In reflecting on my own experiences, I discuss the ways in which health communication is designed to favor post-positivistic research. Through looking at reviewer comments and general academic conversations, I discuss the barriers critical health communication scholars face. In the end, I provide suggestions for ways that critical health communication scholars can move forward as leaders in our subfield.